2021
DOI: 10.1126/sciadv.abe9083
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-modulated three-dimensional electrocatalysts for high-performance fuel cell electrodes

Abstract: Unsupported Pt electrocatalysts demonstrate excellent electrochemical stability when used in polymer electrolyte membrane fuel cells; however, their extreme thinness and low porosity result in insufficient surface area and high mass transfer resistance. Here, we introduce three-dimensionally (3D) customized, multiscale Pt nanoarchitectures (PtNAs) composed of dense and narrow (for sufficient active sites) and sparse (for improved mass transfer) nanoscale building blocks. The 3D-multiscale PtNA fabricated by ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…The development of the modern society is propelled by the renewal and iteration of high-efficiency energy storage techniques (1)(2)(3)(4)(5). Beyond the current lithium-ion batteries, rechargeable zinc-air batteries (ZABs) are regarded as promising next-generation energy storage devices because of their high theoretical energy density (1086 Wh kg −1 , including oxygen) (6,7), low cost (8), inherent safety (using aqueous electrolyte) (9,10), and potential feasibility to achieve high rates and long cycling life span (11).…”
Section: Introductionmentioning
confidence: 99%
“…The development of the modern society is propelled by the renewal and iteration of high-efficiency energy storage techniques (1)(2)(3)(4)(5). Beyond the current lithium-ion batteries, rechargeable zinc-air batteries (ZABs) are regarded as promising next-generation energy storage devices because of their high theoretical energy density (1086 Wh kg −1 , including oxygen) (6,7), low cost (8), inherent safety (using aqueous electrolyte) (9,10), and potential feasibility to achieve high rates and long cycling life span (11).…”
Section: Introductionmentioning
confidence: 99%
“…(e) Schematic illustration and SEM image of multiscale Pt nanoarchitectures. [Reprinted with permission from ref . Copyright 2021, American Association for the Advancement of Science.…”
Section: Block Copolymer Nanopatterning For Nonsemiconductor Applicat...mentioning
confidence: 99%
“…Kim et al successfully demonstrated a high-performance multistacked three-dimensional (3D) Pt catalyst system by introducing Pt nanowires multiple transfer printed on a target substrate. 85 The loading amount and surface area of the resultant catalyst can be modulated to the same level as the commercial Pt/C catalyst (Figure 6c). Usually, conventional catalysts need further support, such as conductive carbon for the electron pathway during the reaction.…”
Section: Block Copolymer Nanopatterning For Nonsemiconductor Applicat...mentioning
confidence: 99%
“…5–9 However, the high oxygen transport resistance at a low Pt loading severely decreases the performance of PEMFCs. 10–12 Density functional theory (DFT) calculations have been employed to understand the underlying mechanisms and optimize the electrodes for enhancing electrochemical reactions. He et al 5 calculated the electronic structure change of catalyst supports when in contact with Pt using DFT calculations and these DFT calculation can serve as an effective screening tool of catalyst supports.…”
Section: Introductionmentioning
confidence: 99%